2021
DOI: 10.1038/s41598-021-99534-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential power of placebo across major psychiatric disorders: a preliminary meta-analysis and machine learning study

Abstract: The placebo effect across psychiatric disorders is still not well understood. In the present study, we conducted meta-analyses including meta-regression, and machine learning analyses to investigate whether the power of placebo effect depends on the types of psychiatric disorders. We included 108 clinical trials (32,035 participants) investigating pharmacological intervention effects on major depressive disorder (MDD), bipolar disorder (BD) and schizophrenia (SCZ). We developed measures based on clinical ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Previous studies have also highlighted the potential of placebobased responses to provide therapeutic outcomes across many clinical conditions [37][38][39] and also to moderate oxytocin based effects [19]. Meta-analyses in the autism field have further supported the existence of placebo responses of a moderate effect size [40].…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have also highlighted the potential of placebobased responses to provide therapeutic outcomes across many clinical conditions [37][38][39] and also to moderate oxytocin based effects [19]. Meta-analyses in the autism field have further supported the existence of placebo responses of a moderate effect size [40].…”
Section: Discussionmentioning
confidence: 96%
“…The magnitude of placebo effect is larger in trials on depressive disorder, bipolar depression and mania, and smaller in trials on schizophrenia 38,39 . Nevertheless, placebo effect has been increasing not only in depression 38 but also in schizophrenia over the past 24 years 189 , and is a major obstacle for developing novel medications 32 .…”
Section: Trends Aimed To De‐risk Trial Programmes Of Novel Agentsmentioning
confidence: 99%
“…While the ingredients driving placebo effect can be studied and have the poten tial to identify safe therapeutic elements that can be exported into clinical care 35 , high placebo response is a plague that af fects RCTs across different mental disor ders 32,38,39 . In fact, it has been suggested that some major pharmaceutical compa nies have diminished their investment in developing medications for mental dis orders because of the challenges in signal detection due to higher than expected pla cebo responses.…”
Section: Placebo Response and Drug-placebo Differencementioning
confidence: 99%
See 1 more Smart Citation
“…Khan and coauthors compared 6 disorders in a 2005 study, which is still the most comprehensive study to date, to our knowledge; however, significant conditions, like mania or social phobia, were not included. Other reviews have focused on depressive disorders or a few other diagnoses …”
Section: Introductionmentioning
confidence: 99%